METHOD COMPRESSION SEGMENTED VIDEO STREAM IN CLUSTERED SPECTRAL-PARAMETRIC SPACE - Elіseev, Evgenіy (Science-based technologies, 2025)
It is shown that in the process of combining different technologies to build complex infrastructure systems, problematic contradictions arise. One of these is the contradiction between certain requirements for the provision of intellectualized video services and the provision of categories of their security and reliability of functioning. This is especially true for technological approaches that use wireless information and network technologies in the presence of cyber attacks. The article states that solutions to this type of contradictions are accompanied by the appearance of the following features: an increase in the complexity of video information flows; increasing the level of their information intensity; increase in pixel volume of video frames. This raises the question of the limited possibility of existing technologies for processing and encoding video data in the conditions of ensuring the quality of video services with the involvement of wireless information and network systems. Accordingly, the performance analysis of existing methods indicates their limited capabilities in terms of encoding complex streams of segmented video data. Hence the need for further development of technologies and methods of video data compression. The option for the development of compression methods is to further improve individual technological stages of JPEG-compatible platforms. Here, as a basic one, it is proposed to choose an approach that is based on reduced redundancies in spectral-parametric space. Hence, it is proposed to use a segmented data flow pre-processing device. This allows you to determine the level of complexity of the content and carry out the stages of its clustering while building adaptive transformations to compress their volume. In this direction, it is necessary to use the technology of processing a segmented video data stream in a unified spectral-parametric space. A technology for compressing a set of transformants of a cluster has been developed, the basic components of which are: formation of a spectral-parametric description of transformants; clustering of the general sequence of transformants; representation of the components of the structural components of the SPOT in differentially normalized space; binary block coding according to the local-monotonic code definition strategy; Generalized code description of the transformant sequence.